Characterization of a new world monopartite begomovirus causing leaf curl disease of tomato in Ecuador and Peru reveals a new direction in geminivirus evolution - Melgarejo, Tomas A; Kon, Tatsuya; Rojas, Maria R; Paz-Carrasco, Lenin; Zerbini, F Murilo; Gilbertson, Robert L (Journal of virology, 2013)
All characterized whitefly-transmitted geminiviruses (begomoviruses) with origins in the New World (NW) have bipartite genomes composed of a DNA-A and DNA-B component. Recently, an NW begomovirus lacking a DNA-B component was associated with tomato leaf curl disease (ToLCD) in Peru, and it was named Tomato leaf deformation virus (ToLDeV). Here, we show that isolates of ToLDeV associated with ToLCD in Ecuador and Peru have a single, genetically diverse genomic DNA that is most closely related to DNA-A components of NW bipartite begomoviruses. Agroinoculation of multimeric clones of the genomic DNA of three ToLDeV genotypes (two variants and a strain) resulted in the development of tomato leaf curl symptoms indistinguishable from those of ToLCD in Ecuador and Peru. Biological properties of these ToLDeV genotypes were similar to those of Old World (OW) monopartite tomato-infecting begomoviruses, including lack of sap transmissibility, phloem limitation, a resistance phenotype in tomato germplasm with the Ty-1 gene, and functional properties of the V1 (capsid protein) and C4 genes. Differences in symptom phenotypes induced by the ToLDeV genotypes in tomato and Nicotiana benthamiana plants were associated with a highly divergent left intergenic region and C4 gene. Together, these results establish that ToLDeV is an emergent NW monopartite begomovirus that is causing ToLCD in Ecuador and Peru. This is the first report of an indigenous NW monopartite begomovirus, and evidence is presented that it emerged from the DNA-A component of a NW bipartite progenitor via convergent evolution and recombination.